Visualizing Oral Infection Dynamics of Beauveria bassiana in the Gut of Tribolium castaneum - Lautaro Preisegger; Juan Cruz Flecha; Fiorella Ghilini; Daysi Espin-Sánchez; Eduardo Prieto; Héctor Oberti; Eduardo Abreo; Carla Huarte-Bonnet; Nicolás Pedrini; Maria Constanza Mannino (Journal of Fungi)
The ability of entomopathogenic fungi, such as Beauveria bassiana, to infect insects by penetrating their cuticle is well documented. However, some insects have evolved mechanisms to combat fungal infections. The red flour beetle (Tribolium castaneum), a major pest causing significant economic losses in stored product environments globally, embeds antifungal compounds within its cuticle as a protective barrier. Previous reports have addressed the contributions of non-cuticular infection routes, noting an increase in mortality in beetles fed with conidia. In this study, we further explore the progression and dynamics of oral exposure in the gut of T. castaneum after feeding with an encapsulated B. bassiana conidia formulation. First, we characterized the formulation surface using atomic force microscopy, observing no significant topological differences between capsules containing and not containing conidia. Confocal microscopy confirmed uniform conidia distribution within the hydrogel matrix. Then, larvae and adult insects fed with the conidia-encapsulated formulation exhibited B. bassiana distributed throughout the alimentary canal, with a higher presence of conidia before the pyloric chamber. More conidia were found in the larval midgut and hindgut compared to adults, but no germinated conidia were observed in the epithelium. These results suggest that the presence of conidia obstructs the gut, impairing the insect’s ability to ingest, process, and absorb nutrients. This disruption may weaken the host, increasing its susceptibility to infections and, ultimately, leading to death. By providing the first direct observation of fungal conidia within the alimentary canal of T. castaneum, this study highlights a novel aspect of fungal–host interaction and opens new avenues for advancing fungal-based pest control strategies by exploiting stage-specific vulnerabilities.